50 Years of Resources Policy – What Is Next? Key Areas of Future Research - Fleming-Munoz, David A.; Campbell, Gary A.; Ley, Yalin; Arratia-Solar, Andrea; Aroca, Patricio A.; Atienza-Ubeda, Miguel; Kumral, Mustafa; Weber, Jeremy; Atienza, Miguel (Elsevier Ltd, 2024)
In 2024, Resources Policy reaches its 50th anniversary as a journal. Fifty years leading the field of mineral and fossil fuel policies and economic research worldwide. Considering this special milestone, we provide a forward-looking view in this paper, highlighting seven areas we believe are critical for robust research that Resources Policy should publish in the future. Leveraging our research expertise and knowledge with the journal, these seven areas of future research include implications of post-mining and energy transitions, the dark side of critical minerals, the increasing substitution of local labour by alternative inputs, the role of the resource curse in resilience considerations, the cleaner production role of mining, macroeconomic frameworks, and the future of mining beyond mines (deep-sea and space mining). We believe more research is needed in these seven research areas, which can enhance our understanding of critical aspects, reduce uncertainty, and provide novel ways to address societal, environmental, economic and policy challenges related to the extraction and use of minerals and fossil fuels. © 2024 Elsevier B.V., All rights reserved.